Teacher’s Leadership in Implementing Learning to Increase Students Learning Effectiveness During Covid-19 Pandemic - Ria Sartika; Yusuf Hadijaya; Nurika Khalila Daulay (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The purpose of this study is to describe teacher leadership in implementing online learning during the pandemic, to describe and explain the implementation of online learning in increasing the effectiveness of student learning during the pandemic, and to find out the inhibiting and supporting factors for the implementation of online learning. This study uses a qualitative research type with a phenomenological approach, the data sources in this study are teachers and students totaling 12 informants. The data collection process is carried out by means of observation, in-depth interviews, and documentation studies, the researcher uses Milles and Huberman analysis techniques with steps of data exposure in the form of words, data reduction, data presentation, and drawing conclusions, after which the validity of the data is checked. credibility, transferability, dependability, and certainty. The results showed that: (1) teacher leadership in implementing online learning during the pandemic at SMP Nur Ihsan Medan went well, the teacher seemed very enthusiastic, more patient in directing students. (2) The implementation of online learning at SMP Nur Ihsan is less effective. (3) The inhibiting factor in carrying out online learning at Nur Ihsan Middle School is the internet network, both because of the device factor, internet quota, and also students' understanding of IT, and the supporting factor is the provision of assistance in the form of internet learning quotas to students and teachers.